Comparison of Performance of SSSC and TCPS in Automatic Generation Control of Hydrothermal System Under Deregulated Scenario - K Subbaramaiah; V.C. Jagan Mohan; V.C.Veera Reddy (Institute of Advanced Engineering and Science, 2011)
This paper presents the modelling and simulation of Static Synchronous Series Compensator (SSSC) in a two area system for Automatic Generation Control (AGC) under deregulated environment. The modelling of Thyristor Controlled phase Shifter (TCPS) is also carried out and comparison is made between SSSC and TCPS. A two area hydrothermal system under deregulated environment has been considered for this purpose. The devices are modeled and attempt has been made to incorporate these devices in the two area system thus improving the dynamic response of the system. The effect of these parameters on the system is demonstrated with the help of computer simulations. A systematic method has also been demonstrated for the modeling of this component in the system. Computer simulations reveal that due to the presence of SSSC along with TCPS, the dynamic performance of the system in terms of settling time, overshoot is greatly improved than that of without SSSC.DOI:http://dx.doi.org/10.11591/ijece.v1i1.21